Družinski oskrbovalci ostarelih staršev in ustvarjanje spola - Šadl, Zdenka (Družboslovne razprave, 2018)
This article employs a gender-sensitive, qualitative and constructionist approach to explore the caregiving experience from the perspectives of women and men who provide informal caregiving services for an ageing parent, with special attention to cultural ideals of femininity and masculinity. Using concepts from the "doing gender" perspective and the concept of hegemonic masculinity, the author explores how the family caregivers in her sample "do" both masculinity and femininity. Qualitative analysis of the transcripts was performed to identify the major themes relating to family caregiving activities, and the ways in which the discursive practices of caregivers reflect how they perform gender. While the women and men in this study did not engage in deep renegotiations of gender identities and relations, they did develop a new identity that supports their caregiving tasks and experiences.
Keywords: družinska oskrba; moškost; ostareli starši; spol; ženskost